2010
DOI: 10.5630/jans.30.2_32
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Development of a Japanease Nurse-manager's Self Evaluation Index

Abstract: This research examined the reliability and validity of the Nursing Management Minimum Data Set in Japan, version1 NMMDS1 , which was developed for nurse managers as a practical self evaluation index. Method The NMMDS1 questionnaire mail survey was conducted from July to October,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Nurse managers and staff nurses (including assistant nurse managers) were recruited to understand interactions between them concerning change processes. A nurse manager has 24‐hour accountability and continuing employee development and directs, plans and coordinates the operational activities for the ward (Oku et al., ). An assistant nurse manager works under the nurse manager to help a nurse manager and has partial responsibility for management in the ward (Teraoka, ).…”
Section: The Studymentioning
confidence: 99%
“…Nurse managers and staff nurses (including assistant nurse managers) were recruited to understand interactions between them concerning change processes. A nurse manager has 24‐hour accountability and continuing employee development and directs, plans and coordinates the operational activities for the ward (Oku et al., ). An assistant nurse manager works under the nurse manager to help a nurse manager and has partial responsibility for management in the ward (Teraoka, ).…”
Section: The Studymentioning
confidence: 99%
“…Furthermore, nurse managers in Japan have less authority than do those in Western countries (Oku et al . , Yoder‐Wise ). Additionally, it is unclear which aspects of the nurse managers’ leadership, based on Bass and Riggio's () theory, are the most effective in increasing staff nurses’ affective commitment.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on leadership have indicated that the cultural context affects the leadership style (Dorfman et al 1997, Den Hartog et al 1999; for example, Asian leaders tend to emphasise group harmony, which is associated with collectivism, while Western leaders focus on values associated with individualism (Dorfman et al 1997, Den Hartog et al 1999). Furthermore, nurse managers in Japan have less authority than do those in Western countries (Oku et al 2010, Yoder-Wise 2011. Additionally, it is unclear which aspects of the nurse managers' leadership, based on Bass and Riggio's (2006) theory, are the most effective in increasing staff nurses' affective commitment.…”
Section: Introductionmentioning
confidence: 99%
“…[1] To assess and improve management competencies, Japanese researchers have developed self-evaluation indices of nursing management competencies. [2,3] However, the number of studies using such standardized indices is limited. Tsukakoshi and colleagues [4] and Tanaka, Taketomi, Yonemitsu, and Kawamoto [5] examined staff development and the competencies required in different managerial roles (e.g., nurse leaders, head nurses, and nursing directors).…”
Section: Introductionmentioning
confidence: 99%